CEGAH MALADMINISTRASI: Fungsi Pengawasan Ombudsman Sulawesi Tenggara di Pelabuhan Feri Kendari-Langara - Arifin Utha; Justawan; Bunga Kartika; Dedi Liswan (Journal Publicuho, 2024)
The aim of this research is to determine the supervisory function of the Ombudsman of the Republic of Indonesia Representative of Southeast Sulawesi in preventing maladministration and improving services at the Kendari-Langara Ferry Port. Using qualitative descriptive research methods. The informants in this research were 2 Heads of Representatives and Prevention Assistants for the Republic of Indonesia Ombudsman for Southeast Sulawesi Province as well as the Head of the Operations Section and UPTD Levy Collection Officer Pel. There were 2 people on the Kendari-Langara Ferry and 2 people from the public/passengers who were determined using a purposive sampling technique. Data collection techniques through in-depth interviews and documentation studies. Interactive data analysis technique according to Milles Humerman and Saldana (2014). The results of the research show that the implementation of supervision by the Indonesian Ombudsman Representative for Southeast Sulawesi on services at the Kendari-Langara Ferry Port has gone well, however, the effectiveness of supervision of services carried out by the Kendari-Langara Ferry Port UPTD, Southeast Sulawesi Province is not good enough as seen from one of the Tangibles indicators. (touchable) has not been met, while the 4 indicators of Reliability, Responsiveness, Assurance and Empathy have been running well in providing services at the Kendari-Langara Ferry Port.